L'Université McGill et la société québécoise francophone, 1951-1969 - Leduc, Bernard (Université de Montréal, 1999)
Keywords: Université McGill

Understanding the Patterns of Language Use of Chinese Children in a Montreal Community School - Curdt-Christiansen, Xiao Lan (Université McGill, 1999)
Keywords: Chinois; Langue; Étudiants

Poésie et discours poétique au Canada français (1889-1909) - Campeau, Sylvain (Université McGill, 1999)
Keywords: Poésie

Narratives and Identities in the Saint Lawrence Valley, 1667-1720 - Gray, Linda Breuer (Université McGill, 1999)

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

St. Lawrence Blvd. as "Third City": Place, Gender and Difference along Montréal's "Main" - Podmore, Julie (Université McGill, 1999)
Keywords: Rues; Saint-Laurent (rue)

The Kahnawake Iroquois and the Lower-Canadian Rebellions, 1837-1838 - Sossoyan, Matthieu (Université McGill, 1999)
Keywords: Autochtones; Iroquois; Rébellions

Rethinking Juvenile Prostitution: Insights from Youths on the Street - Morris, Jason (Université McGill, 1999)
Keywords: Enfants; Prostitution

Labyrinth: Cinema, Myth and Nation at Expo 67 - Whitney, Allison (Université McGill, 1999)
Keywords: Cinéma; Expositions

The Cemetery and Cultural Memory: Montreal Region, 1860 to 1900 - Watkins, Meredith G. (Université McGill, 1999)
Keywords: Cimetières

The Evolution of Prefabricated Interior Components for Post-Occupancy Modification - Ou, Yangli (Université McGill, 1999)

Coping with the HIV and AIDS Epidemic in HIV Seronegative Gay Males in Montreal - Watson, Scott C. A. (Université McGill, 1999)
Keywords: Épidémies

Broadway North: Musical Theatre in Montreal in the 1920s - Charpentier, Marc (Université McGill, 1999)
Keywords: Musique; Théâtre

A Neighborhood that Empowers Women: In Search of Housing Sustainability - Insaf, Zeenat S. (Université McGill, 1999)
Keywords: Femmes; Logement